2021
DOI: 10.1112/s0010437x20007630
|View full text |Cite
|
Sign up to set email alerts
|

On dualizability of braided tensor categories

Abstract: We study the question of dualizability in higher Morita categories of locally presentable tensor categories and braided tensor categories. Our main results are that the 3-category of rigid tensor categories with enough compact projectives is 2-dualizable, that the 4-category of rigid braided tensor categories with enough compact projectives is 3-dualizable, and that (in characteristic zero) the 4-category of braided multi-fusion categories is 4-dualizable. Via the cobordism hypothesis, this produces respective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…It is clear that this isomorphism preserves coproduct, counit and unit and the only nontrivial check is that the product is preserved as well. The relations (18), (19) in 31 are clearly satisfied. For (20), the claim follows from Theorem 5.22.…”
Section: Proposition 516mentioning
confidence: 90%
See 3 more Smart Citations
“…It is clear that this isomorphism preserves coproduct, counit and unit and the only nontrivial check is that the product is preserved as well. The relations (18), (19) in 31 are clearly satisfied. For (20), the claim follows from Theorem 5.22.…”
Section: Proposition 516mentioning
confidence: 90%
“…Since is monoidal, the objects are also dualisable. But we have just shown that such objects are the generating compact projective objects, while by [18, Proposition 4.1], it is enough to check cp-rigidity on the generating compact projective objects.…”
Section: Harish-chandra Bimodulesmentioning
confidence: 99%
See 2 more Smart Citations
“…In that setting, the 4-dimensional Crane-Yetter-Kauffman TFT carries a boundary theory given by the 3dimensional Witten-Reshetikhin-Turaev TFT, a mathematical incarnation of Chern-Simons theory for the compact form of G. It seems natural to view Walker's TFT associated to the ribbon category Rep q (G) with q generic in the context of analytically continued Chern-Simons theory as discussed in [95]. (2) The work [18] constructs a 3-2-1-0 TFT for an arbitrary rigid braided tensor category. It is conjectured there that for semi-simple ribbon categories their construction coincides with Walker's 3-2 TFT.…”
Section: Topological Field Theorymentioning
confidence: 99%